Reconsidering domestication from a process archaeology perspective. Issue 1 (1st January 2021) - Bogaard, Amy; Allaby, Robin; Arbuckle, Benjamin S.; Bendrey, Robin; Crowley, Sarah; Cucchi, Thomas; Denham, Tim; Frantz, Laurent; Fuller, Dorian; Gilbert, Tom; Karlsson, Elinor; Manin, Aurélie; et al.
ABSTRACT: Process philosophy offers a metaphysical foundation for domestication studies. This grounding is especially important given the European colonialist origin of 'domestication' as a term and 19th century cultural project. We explore the potential of process archaeology for deep-time investigation of domestication relationships, drawing attention to the variable pace of domestication as an ongoing process within and across taxa; the nature of domestication 'syndromes' and 'pathways' as general hypotheses about process; the importance of cooperation as well as competition among humans and other organisms; the significance of non-human agency; and the ubiquity of hybrid communities that resist the simple wild/domestic dichotomy.